1999
DOI: 10.1083/jcb.146.6.1303
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Apc2 Is a Cytoskeletally-Associated Protein That Regulates Wingless Signaling in the Embryonic Epidermis

Abstract: The tumor suppressor adenomatous polyposis coli (APC) negatively regulates Wingless (Wg)/Wnt signal transduction by helping target the Wnt effector β-catenin or its Drosophila homologue Armadillo (Arm) for destruction. In cultured mammalian cells, APC localizes to the cell cortex near the ends of microtubules. Drosophila APC (dAPC) negatively regulates Arm signaling, but only in a limited set of tissues. We describe a second fly APC, dAPC2, which binds Arm and is expressed in a broad spectrum of tissues. dAPC2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
200
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 175 publications
(218 citation statements)
references
References 47 publications
(75 reference statements)
18
200
0
Order By: Relevance
“…In Drosophila APC2, the Arm repeats play key roles in Wnt signaling (McCartney et al 2006;Hamada and Bienz 2002;McCartney et al 1999). Both the Arm repeats and the region including the 20-aa and SAMP repeats are important for APC2's cortical localization (McCartney et al 2006), supporting the hypothesis that APC2 acts at the cortex in Wnt regulation and suggesting the existence of an unidentified cortical partner.…”
Section: Deconstructing the Destruction Complexmentioning
confidence: 51%
See 2 more Smart Citations
“…In Drosophila APC2, the Arm repeats play key roles in Wnt signaling (McCartney et al 2006;Hamada and Bienz 2002;McCartney et al 1999). Both the Arm repeats and the region including the 20-aa and SAMP repeats are important for APC2's cortical localization (McCartney et al 2006), supporting the hypothesis that APC2 acts at the cortex in Wnt regulation and suggesting the existence of an unidentified cortical partner.…”
Section: Deconstructing the Destruction Complexmentioning
confidence: 51%
“…Thus, the clearest picture came from studying APC. Both mammalian APC (Näthke et al 1996) and Drosophila APC2 (McCartney et al 1999;Yu et al 1999) are enriched at the cortex of epithelial cells, suggesting this may be the normal location of the destruction complex. Consistent with this, missense mutations in fly APC2 exhibit a strong correlation between loss of cortical protein localization and loss of function in Wnt regulation (McCartney et al 2006).…”
Section: Pip5kmentioning
confidence: 99%
See 1 more Smart Citation
“…Peifer and colleagues tested the ability of various Drosophila APC2 mutants to rescue b-catenin destruction in SW480 cells, and their effects in flies lacking APC2 only or both APC1 and APC2. Note that APC2 is the major form in fly embryos, but in single APC2 mutants, APC1 provides residual activity such that levels of b-catenin are only slightly elevated, producing effects on cell fate but not leading to complete nonviability (McCartney et al 1999). By deleting R2 and/or the CID to prevent b-catenin destruction, Roberts et al (2011) could assess the function of b-catenin-binding activity of the 15-mers and the other 20-mer repeats.…”
Section: Sequestration Of B-cateninmentioning
confidence: 99%
“…A pool of APC localizes to the basolateral cortex or cell-cell junctions of vertebrate epithelial cells and tissues, and Drosophila APC2 likewise localizes to the cell cortex through interactions with the microtubule and actin cytoskeletons (Näthke et al 1996;McCartney et al 1999McCartney et al , 2006Yu et al 1999;Rosin-Arbesfeld et al 2001;Langford et al 2006a,b;Grohmann et al 2007;Zhou et al 2011). In studies of nuclear export by APC, it was found that truncated APCs lacking cytoskeletal interaction regions shuttle between the nucleus and cytoplasm more efficiently than the full-length protein, suggesting that cytoskeletal interactions help to retain APC in the cytosol (Brocardo et al 2005), consistent with a role in cytoplasmic retention of b-catenin.…”
Section: Destruction Complex Localizationmentioning
confidence: 99%